Strategies Used by English Teachers in Teaching Vocabulary - Endah Fauziningrum; Mike Nurmalia Sari; Sofia F Rahmani; Rinda Riztya; Syafruni Syafruni; Pria Mitra Purba (Departement of Mathematics Education, 2023)
English-language higher education instruction in non-English-speaking nations is now a reality in a number of locales. Teachers that are leading the way in teaching English need to have the best teaching methods, particularly when it comes to teaching vocabulary. To meet learning objectives, techniques and their justifications must be obvious. To address these issues, the researchers employed a qualitative technique and a descriptive research design. English instructors were the study's subject. based on examination of the documentation, interview, and observation. According to the study's findings, (1) both of the English teachers at MTsS Siulak Gedang employed dictionaries and translation techniques to teach their pupils vocabulary. (2) The explanations provided by teachers for their usage of the translation approach include the methods suit their teaching materials and it is easy to conduct.